A review of sexual strategies in Cannabis sativa L. under genomic and environmental controls - Yousoon Baek; Daniela Vergara (Agrosystems, Geosciences & Environment)
Abstract Cannabis sativa L. (marijuana, hemp) is one of the few dioecious angiosperm species with sex chromosomes. Along with other closely related genera from the family Cannabaceae, C. sativa exhibits monoecious (unisexual flowers at different locations within the individual) and dioecious (two sexes in separate individuals) populations. Despite recent progress in understanding the plant's biology, its sexual strategies are still not fully understood and key advancements such as complete genome assemblies that include the Y and monoecious chromosomes are still lacking. Here, we summarize the diverse reproductive strategies within angiosperms focusing on the family Cannabaceae—with members that have varying sex chromosome number—and specifically on C. sativa. We include the characterization of the non‐recombining and pseudoautosomal regions of the Y chromosome, the different size estimates of the sex chromosomes, and the multiple genetic markers that have been developed for sex determination in C. sativa. We then describe the genetic and environmental factors influencing sex expression in C. sativa, with external factors presenting practical applications in agriculture systems such as the production of “feminized seeds” through sex reversal techniques. Additionally, important agricultural characteristics between males, females, and monoecious plants emphasize the importance of sex determination for fiber quality and medicinal applications. This comprehensive overview of sex determination in C. sativa contributes significantly to the understanding of this complex and economically important plant, offering valuable insights for researchers and cultivators in this nascent industry.